The Role of Traditional Elders in the Establishment of the law and order in FATA, PAKISTAN - Shahid Iqbal; Intikhab Alam (الإيضاح, 2020)
This study was carried out in Khyber Agency (FATA), with the main objective to determine the tribal thoughts towards the role of traditional elders in the establishment of law and order. The data was collected from randomly selected 380 sampled respondents, which includes people from commerce/trade community, students, Internally Displaced Persons (IDPs) and representatives from political administration was randomly drawn. To see the association between independent and dependent variables chi square statistics was used. The study reveals that the local people were not happy with the Malaks’ role (traditional local leaders) for the reason of their personal interests which sustained their subjugation. It further indicates that the Malaks’ role was weakened by the stronger influence of insurgents and even their tax collection act in view of the prevalent poor law and order situation. However, the Malaks’ role was double-edged as they got benefits from the political administration on the one hand and looked for the insurgents’ help in different issues on the other. Tribal elders remained silent over misdeed in the area. The local Malaks are enjoying like bourgeoisie class as political administration and masses are bound to go in accordance with their directions. They are not facing any kind of accountability for the financial benefits awarded by the political administration. The locals were found with oppressed feelings caused by the suppressive role of Malaks. Frontier crime Regulation (FCR) which is a tribal law has enshrined power to the local Malaks and political administration. The state law, which is not in vogue in the entire tribal belt, was observed as the only mechanism to bring normalcy by narrowing the spectrum of the Malaks’ role and political administration. The local bourgeoisie (Malakān), operating around with all might’s being enjoyed and exercised on their parts through a strong endorsement from the administration needs not to be overlooked. Their role must be defined under the provision of state law enshrined through constitutional cover. This would make them accountable and sense of accountability always brings honesty, dedication and loyalty. Moreover, oppressed feeling surfaced during the study from the local masses regarding the role of these Malak would also brought under the umbrella of check and balance and thus a democratic norms would prevail in aftermath.